PROFIL PEMBANTU PADA RUMAH TANGGA WARGA NEGARA ASING DI KOMPLEKS PERUMAHAN CPI KELURAHAN PEMATANG PUDU KECAMATAN MANDAU KABUPATEN BENGKALIS - Septiani, Tika; Razif, M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research was conducted in the Village Causeway Pudu Mandau sub Bengkalis. The purpose of this study was to identify the profile of the domestic helper foreign nationals. This study entitled